Researching Dreams The Fundamentals - Schredl, Michael (Springer International Publishing, 2018)
What can be gleaned from the study of our dreams? The book not only presents a comprehensive introduction to the research obtained so far but also provides the tools to carry our scientific dream studies-including the shortcomings and strengths of various approaches. Topics include the factors of dream recall; the continuity hypothesis of dreaming; the relationship between physiology and dream content; etiology and therapy of nightmares; and lucid dreaming.